Penggunaan Kessler psychological distress scale, food recall dan food frequency questionnaire dalam menentukan faktor predisposisi recurrent aphthous stomatitis - Dewi, Ayu Galih Permata; Herawati, Erna; Wahyuni, Indah Suasani (Jurnal Kedokteran Gigi Universitas Padjadjaran, 2017)
Pendahuluan: Recurrent Aphtous Stomatitis merupakan kelainan mukosa rongga mulut, dengan ulser berbatas regular secara berulang. Etiologi belum diketahui, tetapi ada beberapa faktor predisposisi yang dapat menginisiasi, antara lain defisiensi nutrisi dan stres. Tujuan artikel ini untuk membahas kasus Recurrent Aphtous Stomatitis minor terkait defisiensi nutrisi dan stres emosional. Laporan Kasus: Wanita, 23 tahun mengeluhkan sariawan pada bibir, sakit saat makan dan berulang 2 bulan sekali. Pasien jarang makan sayur dan buah, serta banyak pekerjaan. Secara klinis ulser berdiameter 2mm, ditutupi pseudomembran putih kekuningan, dengan margin regular pada mukosa labial kanan atas. Pasien didiagnosis Recurrent Aphtous Stomatitis minor dan diterapi dengan Triamsinolone acetonide 0,1% gel. Faktor predisposisi yaitu stress diukur dengan kuisioner Kessler Psychological Distress Scale, dan asupan nutrisi diukur dengan kuisioner Food Recall 24 jam dan food frequency questionnaire. Hasil: Tingkat stres skala 35 dikategorikan stres berat. Berdasarkan kuisioner kecukupan gizi pasien mengalami defisiensi nutrisi terutama asam folat dan zat besi. Penyembuhan terjadi lebih lama, sekitar 16 hari, dibandingkan Recurrent Aphtous Stomatitis pada umumnya. Simpulan: Penggunaan Kessler Psychological Distress Scale, Food Recall dan Food Frequency Questionnaire dapat menentukan faktor etiologi dan membantu dalam tatalaksana Recurrent Aphtous Stomatitis.Â The usage of Kessler psychological distress scale, food recall, and food frequency questionnaire in determining predisposing factors of recurrent aphthous stomatitisÂ ABSTRACTIntroduction: Recurrent Aphthous Stomatitis was a common disorder in oral mucosa, signed by recurrent ulcer with regular margin. The aetiology was unknown, but there were such predisposing factors initiated the disease, one of them were nutrient deficiency and stress. The purpose of this article was to reported the Recurrent aphthous stomatitis minor case related to nutrient deficiency and stress emotional. Case Report: A young woman, 23-years-old with chief complaints of mouth ulcers, chewing illness, and all recurrent symptoms every 2 months. The woman had many school tasks, with seldom fruits and vegetable consumption. Clinically, the ulcersâ diameter was 2mm, with regular margin covered with white-yellowish pseudomembrane at the upper labial mucosa. The patient was diagnosed Recurrent Aphthous Stomatitis minor and treated using 0.1% Triamcinolone acetonide gel. The expected predisposing factors were nutrient deficiency and stress, which were measured with the Kessler Psychological Distress Scale for the stress level, and the 24 hours food recall and food frequency questionnaire for the nutrient intake. Results: The stress level score was 35 and classified as severe categories. Based on the nutrition questionnaire, the patient had a nutrient deficiency, especially folic acid and iron. The healing process was quite long compared to the general healing time, approximately in 16 days. Conclusion: The use of Kessler Psychological Distress Scale, Food Recall, and Food Frequency Questionnaire could determine the aetiology factors and assisted the management of Recurrent aphthous stomatitis.Keywords: Recurrent aphthous stomatitis minor, kessler psychological distress scale, food recall questionnaire, food frequency questionnaire.